Hiking waterfalls Montana : a guide to the state's best waterfall hikes - Kratz, John (John Lawrence) (Hiking waterfalls, 2022)
"Fully revised and updated, Hiking Waterfalls Montana, Second Edition includes detailed hike descriptions, maps, and color photos for 100 of the state's most scenic waterfall hikes"--